KAJIAN LITERATUR: HUBUNGAN ANTARA STATUS GIZI DENGAN POLA TIDUR TERHADAP KEJADIAN ANEMIA PADA REMAJA PUTRI PADA WILAYAH PESISIR PANTAI - Steviola Hevanda (CV. ADIBA AISHA AMIRA, 2023)
Hemoglobin levels that are less than normal levels are often referred to as Anemia. The result of a lack of hemoglobin in the body becomes a lack of oxygen which makes the sufferer pale and tire easily. According to WHO, the incidence of anemia in young women is around 53.7%. In this study the researchers intended to examine the relationship between nutritional status and sleep patterns on the incidence of anemia in young women. This study used the literature review method for 2000-2022 with a descriptive analysis approach using a systematic review design, namely by searching journal articles on the Google Scholar database with the keywords anemia, young women, sleep patterns, and nutritional status. The results obtained by researchers on nutritional status have a correlation with the incidence of Anemia, while sleep patterns have no results from related studies.